2020
DOI: 10.18203/issn.2455-4510.intjresorthop20203728
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional outcome of elastic stable intramedullary nailing in pediatric femoral fractures in the age group of 5-16 years

Abstract: <p class="abstract"><strong>Background:</strong> Fractures of the femur are the most incapacitating fractures. The best treatment for children between five to sixteen years of age is still debated. The ESIN has the benefits of early immediate stability to the involved bone segment, permitting early mobilization and return to the normal activities of the patients, respect for the physes, minimal scarring with lower complications. The purpose of this study was to present this study results foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…Femoral shaft fractures are the utmost communal pediatric injuries managed by an orthopaedic surgeon. Management is in luenced by trauma or multiple injuries, personality breakdowns, age, family problems and costs (Misaghi et al, 2020;Edwin et al, 2020;Curran et al, 2020). Spica cast ixation is an effective, safe and simple treatment for pediatric femoral shaft fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Femoral shaft fractures are the utmost communal pediatric injuries managed by an orthopaedic surgeon. Management is in luenced by trauma or multiple injuries, personality breakdowns, age, family problems and costs (Misaghi et al, 2020;Edwin et al, 2020;Curran et al, 2020). Spica cast ixation is an effective, safe and simple treatment for pediatric femoral shaft fractures.…”
Section: Discussionmentioning
confidence: 99%
“…According to Flynn score criteria, 16 excellent clinical outcomes were noted in 85.3% (29/34) cases and 14.7% cases (05/34) showed satisfactory outcome (Table 3). occasions when the contouring is not satisfactory, an additional nail is used to add stability to the reduction.…”
Section: Functional Outcomementioning
confidence: 96%
“…A recent study also showed that patients who weigh above 45 kg have a higher chance of fracture displacement (10) . Most complications of using the ESIN technique are related to the surgeon, patient selection, and surgical technique (improper size nail, improper placement of the nail, or inadequate cutting of exposed nail) (11) .…”
Section: Introductionmentioning
confidence: 99%